High-Grade Spindle Cell Sarcoma of the Heart - Jay P. Natarajan, BS; Ashorne K. Mahenthiran, BA; Anil K. Ranginani, MD; Jo Mahenthiran, MD (JACC: Case Reports, 2019)
A young female with pulmonary congestion suspected to be secondary to mitral valve disease with left atrial appendage thrombus was given therapy for heart failure and anticoagulation. Subsequent multimodality imaging with echocardiography and magnetic resonance imaging established an accurate but rare diagnosis of spindle cell sarcoma of the heart. (Level of Difficulty: Intermediate.)